2008
DOI: 10.1177/0269881107081559
|View full text |Cite
|
Sign up to set email alerts
|

Is aripiprazole the only choice of treatment of the patients who developed anti-psychotic agents-induced leucopenia and neutropenia? A case report

Abstract: Leucopenia and neutropenia could be side effects of anti-psychotic drugs, especially clozapine. However, there is evidence that other anti-psychotics can cause leucopenia and neutropenia. We present the clinical follow-up and treatment process of a patient, who had initially developed quetiapine and amisulpride related neutropenia, but not with aripiprazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…There has been no report of neutropenia associated with aripiprazole as a single agent. In addition, some case reports suggested that aripiprazole can be used in the case of antipsychotic-induced neutropenia 5,9. However, it needs to be reconsidered because, similar with our case, aripiprazole-induced neutropenia subsequent to other antipsychotic-induced neutropenia were reported 10…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…There has been no report of neutropenia associated with aripiprazole as a single agent. In addition, some case reports suggested that aripiprazole can be used in the case of antipsychotic-induced neutropenia 5,9. However, it needs to be reconsidered because, similar with our case, aripiprazole-induced neutropenia subsequent to other antipsychotic-induced neutropenia were reported 10…”
Section: Discussionsupporting
confidence: 78%
“…However, neutropenia has also been reported when patients were treated with other second generation antipsychotics such as olanzapine,2 quetiapine,3 risperidone,4 and amisulpride 5. Although the risk of these individual medicines has been documented, it is still not clear whether the risk of neutropenia is further increased when a patient is sequentially treated with different antipsychotics.…”
Section: Introductionmentioning
confidence: 99%
“…Neutropenia (nadir 1.1 L −9 ) brought on by quetiapine (up to 600 mg/d) accompanied by thrombocytopenia (nadir 146 L −9 ) has been described (Shankar, 2007). In a further patient, neutropenia (nadir 1.4 L −9 ) was manifest on day 7 of quetiapine treatment (400 mg/d), and recovered to 2.5 L −9 5 days after stopping the drug (Yalcin et al ., 2008). Subsequent treatment with amisulpride (400 mg/d, 2 d) was accompanied by a neutrophil count of 1.8 L −9 and amisulpride was stopped as well—this seems unlikely to be an effect of this latter drug since (i) exposure was very brief and (ii) amisulpride has hardly ever been implicated as a cause of neutropenia/agranulocytosis.…”
Section: Neutropenia/agranulocytosis With Antipsychotics Other Than Cmentioning
confidence: 99%
“…3 In a German national study, leukocytopenia seems to be mostly induced by clozapine (0.18% patients exposed) and olanzapine/risperidone at lower proportions. 6 The relatively pure dopamine-affinity profile for amisulpride or aripiprazole might be a possible mechanism for lowering the risk of leukocytopenia or neutropenia. 5 It suggests that most second-generation antipsychotics still have the risk for leukocytopenia.…”
Section: Discussionmentioning
confidence: 99%